2021
DOI: 10.3390/vaccines9091016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Attitudes and Beliefs Concerning Vaccination and Influenza Vaccines between the First and Second COVID-19 Pandemic Waves: A Longitudinal Study

Abstract: Perceptions of the risks of vaccine-preventable diseases and preventive behaviors change over time. The ongoing COVID-19 pandemic may have modified laypeople’s attitudes towards routine vaccinations. In this longitudinal study, we aimed to assess changes in attitudes and beliefs concerning (influenza) vaccines between the first and second COVID-19 pandemic waves. A total of 1979 participants completed both 2020 and 2021 surveys. After one year, more interviewees agreed that vaccines were fundamental and should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 39 publications
4
49
3
2
Order By: Relevance
“…Indeed, only 23% of adult Italians would willingly accept concomitant immunization, while 17% would absolutely not; the remaining majority (approximately 60%) may be dubbed as hesitant to some degree. The number of co-administration-hesitant individuals proved to be higher than that of the SIV-hesitant subjects recorded in our previous studies [11,18] on the acceptance of SIV alone. A similar tendency has been reported with regard to pediatric vaccinations: in Italy, vaccinehesitant individuals are less favorable toward using combined vaccines and vaccine coadministration [24].…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Indeed, only 23% of adult Italians would willingly accept concomitant immunization, while 17% would absolutely not; the remaining majority (approximately 60%) may be dubbed as hesitant to some degree. The number of co-administration-hesitant individuals proved to be higher than that of the SIV-hesitant subjects recorded in our previous studies [11,18] on the acceptance of SIV alone. A similar tendency has been reported with regard to pediatric vaccinations: in Italy, vaccinehesitant individuals are less favorable toward using combined vaccines and vaccine coadministration [24].…”
Section: Discussioncontrasting
confidence: 67%
“…Increasing age is usually associated with a higher vaccine acceptance [16,17,30,[33][34][35][36]. In our previous survey rounds [11,18], both SIV uptake and acceptance were higher in older individuals. By contrast, in this study an inverse age-acceptance relationship was observed: each 1-year increase in age was associated with a 1.1% decrease in the odds of accepting simultaneous vaccine administration.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Acceptance of SIV and COVID-19 vaccines is interrelated. On the one hand, previous experience of SIV increases the likelihood of receiving COVID-19 vaccines; on the other hand, the uptake of SIV may increase as a consequence of the ongoing COVID-19 pandemic [45] , [46] . We believe that integrating messages regarding non-specific vaccine effects into a promotional communication mix could help to convince some hesitant HCWs, thereby increasing vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%